(untitled) (Journal of Geography and Environmental Management, 2025)
Soil is one of the main resources of the human habitat. Nevertheless, the choice of economic growth as a priority for development in the period after the scientific and technological revolution led to depletion and significant pollution of the soil. Pollution occurs in different ways, and the relevance of monitoring the pollution process is obvious in order to preserve soil fertility and increase yields. Soil pollution occurs when the amount of certain soil elements and other substances exceeds the recommended levels for human, animal or plant life. The article summarizes and differentiates the causes and consequences of man-made pollution as a result of increased anthropogenic impact on the soil cover of the Kyzylorda region, an agricultural and industrial zone located in the south-west of the Republic of Kazakhstan, by conducting a review and analysis of domestic and foreign freely available scientific literature. It has been established that the main sources of pollutants of a technogenic nature of the soil cover of the Aral Sea region are radionuclides, oil and petroleum products, urbanized zones and fuel components of launch vehicles. During the review, it was shown that the state of the biological resources of the region is under the close attention of the world scientific community. To some extent, this may be a side effect of the Aral Sea and the Baikonur cosmodrome located in the region